Structure, morphology, and optical properties of ZnO:Mg thin film prepared by sol-gel spin coating method - Astuti, Budi; Marwoto, Putut; Zhafirah, Azizah; Hamid, Nur; Aryanto, Didik; Sugianto, Sugianto; Sulhadi, Sulhadi; Putra, Ngurah Made Dharma; Fianti, Fianti (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
This research was conducted to analyze the Mg doping concentration effect on the structure, morphology, and optical properties of ZnO thin film prepared using the sol gel spin coating method. The Mg concentration was varied in the mole fraction of 1%, 3%, and 5%. Firstly, ZnO: Mg solution was dropped on a substrate and grown with a rotating speed of 3000 rpm and then annealed at 500 °C for 2 hours. The characterization of thin films' structure, morphology, and optical properties was done using XRD, FESEM, EDX, and UV-VIS spectrophotometer. XRD result showed a polycrystalline structure with three dominant peaks of (100), (002), and (101) plane, hexagonal wurtzite structures. Furthermore, the crystallite size was increased with the increase of Mg doping. FESEM results showed that the 5% ZnO: Mg thin film was the densest and least void from other films. In addition, the results of UV-Vis-NIR analysis showed the highest absorption value at a wavelength of 360-370 nm. The bandgap energy increased at 1% and 3% Mg doping samples but decreased by 5% Mg doping comes from the excess of oxygen in thin film with 5% Mg doping.